Corneo‐limbo‐conjunctival transposition to treat deep and perforating corneal ulcers in dogs: A review of 418 eyes and corneal clarity scoring in 111 eyes. (9th October 2020) - Cebrian, Prado; Escanilla, Natalia; Lowe, Robert C.; Dawson, Charlotte; Sanchez, Rick F.
Abstract: Purpose: To report surgical and corneal clarity scores (CCSs) of corneo‐limbo‐conjunctival transpositions (CLCTs) in a large number of canine cases. Methods: Retrospective review of records that underwent CLCT to repair deep ulcers or perforations between 2002 and 2018. Signalment, concurrent eye disease, additional procedures, pathogenesis, medication, graft orientation, follow‐up, and CCSs were recorded. Results: 418 eyes of 399 dogs were included. Brachycephalics were most commonly affected, comprising 325/418 (77.75%) of the eyes. The most commonly affected breeds were Pugs, Shih Tzus, Cavalier King Charles Spaniels, and French Bulldogs, with 116/418 (27.75%), 64/418 (15.31%), 34/418 (8.13%), and 34/418 (8.13%) ulcerated eyes, respectively. Mean age at surgery was 5.5 years (range 59 days‐17.7 years), and median follow‐up time was 100 days (range 3 days‐7.64 years). The most common etiopathogenesis was spontaneous ulceration in 205/418 eyes (49.04%) of which 191 (93.17%) occurred in brachycephalics. Primary keratoconjunctivitis sicca affected 122/418 eyes (29.19%) and injury 39/418 eyes (9.33%). Mean ulcer width was 3.5 mm (0.5‐10 mm). Success rate was 97.13% (406/418 eyes). Failure end points recorded included no menace response, secondary glaucoma, and endophthalmitis. Pre‐existing perforation was found in 101/418 (24.16%) of the eyes and significantly increased failure rate ( P  < .001). The median CCS was G3 (G0‐G4), which was lower for Pugs (G2). Graft orientation affected CCS, but did not reach statistical significance. Conclusion: The high success rate and CCS for CLCT in dogs make it a good technique to treat deep ulcers but a less desirable outcome is anticipated when treating perforations and Pugs.